City ideologies in techno-urban imaginaries - Salerno, Rosella (Urban, 2016)
AbstractThe idea of the city has been transformed over the past two decades under the drive of information technology and communications, creating a shift between the built city and communities that no longer seem so respecting the paradigm that for ages has seen them coincide in the same place. If the city -as a community - can today be so undocked from its physical structures, in parallel communication devices can generate new urban dimensions strongly influenced by technology. The paper intends to critically investigate how ICT contribute, beyond any rhetoric about hyper-technological innovation, in creating a new urban ideology (or post-urban) from the new forms of use and the imaginary that they bring to. KeywordsUrban and social space; digital media; urban imaginary; ideals in urban technologies